Matematyka
kasiulkaa
2017-06-24 10:11:35
1)Oblicz; a) (3^1/2*3^-1,25:3^3/4)^3/4 b)(27^1/6)^-2 c)+49^1/5)^5/2 d)(7^-0,7:7^2/5*7^0,9)^1/2 e)[(6^1/3)^2:6^-1/3]^2:4^0,5 f) [4^1/3*(0,5)^-1/3]^-2 2) Oblicz: a)32^4/5 b)49^1/2 c)(0,25)^-1/2 d)64^4/3 e)0,0016^1/4
Odpowiedź
pati8007
2017-06-24 10:21:55

wzory [latex]a^ncdot a^m = a^{n+m}\ a^n:a^m = a^{n-m}\ (a^n)^m = a^{ncdot m}[/latex] zad.1 [latex]a) (3^{frac{1}{2}}*3^{-1,25}:3^{frac{3}{4}})^{frac{3}{4}} = (3^{frac{1}{2}+(-frac{5}{4})-frac{3}{4}})^{frac{3}{4}}=(3^{-frac{6}{4}})^{frac{3}{4}} = 3^{-frac{9}{8}} \ \ b) (27^{frac{1}{6}})^-2 = 27^{-frac{1}{3}} = (3^3)^{-frac{1}{3}}=3^{-1}\ \ c) (49^{frac{1}{5}})^{frac{5}{2}} = 49^{frac{1}{2}} = (7^2)^{frac{1}{2}}=7\ \ [/latex] [latex]d) (7^{-0,7}:7^{frac{2}{5}}*7^{0,9})^{frac{1}{2}} = (7^{(-0,7-0,4+0,9)})^{frac{1}{2}} = 7^{-0,2})^{frac{1}{2}} = (7^{-frac{1}{5}})^{frac{1}{2}}=7^{-frac{1}{10}}\ \e) [(6^{frac{1}{3}})^2:6^{-frac{1}{3}}]^2:4^{0,5} = (6^{frac{2}{3}}: 6^{-frac{1}{3}})^2:4^{0,5}=6^{frac{2}{3}}:4^{frac{1}{2}}=\=(2cdot 3)^{frac{2}{3}}:(2^2)^{frac{1}{2}}=2^{frac{2}{3}}cdot 3^{frac{2}{3}}:2 = 2^{-frac{1}{3}}cdot 3^{frac{2}{3}}\ \ [/latex] [latex]f) [4^{frac{1}{3}}*(0,5)^{-frac{1}{3}}]^{-2} = [(2^2)^{frac{1}{3}}*(2^{-1})^{-frac{1}{3}}]^{-2}==(2^{(frac{2}{3}+frac{1}{3})})^{-2}=2^{-2} [/latex] zad.2 [latex]a) 32^{frac{4}{5}}=(2^5)^{frac{4}{5}}=2^4=16\ \ b) 49^{frac{1}{2}}=(7^2)^{frac{1}{2}}=7\ \ c) (0,25)^{-frac{1}{2}}=(frac{1}{4})^{-frac{1}{2}}= (4^{-1})^{-frac{1}{2}} = 4^{frac{1}{2}}=(2^2)^{frac{1}{2}} = 2\\ d) 64^{frac{4}{3}}=(4^3)^{frac{4}{3}}= = 4^4 = 256\ \ e) 0,0016^{frac{1}{4}}=(0,2^4)^{frac{1}{4}}=0,2[/latex]

Dodaj swoją odpowiedź